Banking reform and the Federal Reserve, 1863-1923 - West, Robert Craig (Ithaca : Cornell University Press, 1977)
In this book, attempt is made to shed some light on the early years of the Federal Reserve System.
Includes index.
Bibliography: p. [231]-239.
osc 19/9/17
Loans
Keywords: Federal Reserve banks; Banks and banking